Does increasing immunoglobulin levels impact survival in solid organ transplant recipients with hypogammaglobulinemia?. (15th October 2014) - Florescu, Diana F.; Kalil, Andre C.; Qiu, Fang; Grant, Wendy; Morris, Michael C.; Schmidt, Cynthia M.; Florescu, Marius C.; Poole, Jill A.
Abstract Background Severe hypogammaglobulinemia (IgG < 400 mg/dL) has adverse impact on mortality during the first year post‐transplantation. The aim of the study was to determine whether increasing IgG levels to ≥400 mg/dL improved outcomes. Methods Kaplan–Meier analyses were performed to estimate survival, log‐rank test to compare survival distributions between groups, and Fisher's exact test to determine the association between hypogammaglobulinemia and rejection or graft loss. Results Thirty‐seven solid organ transplant (SOT) recipients were included. Hypogammaglobulinemia was diagnosed at median of 5.6 months (range: 0–291.8 months) post‐transplantation. Types of transplants: liver–small bowel (17); liver–small bowel–kidney (2); liver (5); small bowel (4); liver–kidney (1); kidney/kidney–pancreas (3); heart (3); heart–kidney (1); and heart–lung (1). The three‐yr survival after the diagnosis of hypogammaglobulinemia was 49.5% (95% CI: 32.2–64.6%). Patients were dichotomized based upon IgG level at last follow‐up: IgG ≥ 400 mg/dL (23 patients) and IgG < 400 mg/dL (14 patients). There was no evidence of a difference in survival (p = 0.44), rejection rate (p = 0.44), and graft loss censored for death (p = 0.99) at one yr between these two groups. There was no difference in survival between patients receiving or not immunoglobulin (p = 0.99) or cytomegalovirus hyperimmunoglobulin (p = 0.14). Conclusion Severe hypogammaglobulinemia after SOT is associated with high mortality rates, but increasing IgG levels to ≥400 mg/dL did not seem to translate in better patient or graft survival in this cohort.